Craniosacral Therapy for Migraine and Headache: Three Case Reviews - Bernstein MD, Carolyn; Fan-Roche, Jie (Indian Journal of Integrative Medicine, 2023)
Craniosacral Therapy is a touch therapy with osteopathic roots. There is little research to date although effects on various types of headaches and pain have been described. In this case series, we discuss the treatment of three patients with headaches who were successfully treated with CST (craniosacral therapy) after reviewing the techniques, and we cite the need for further research.